The Impact of USAID Budget Cuts on Global Development Initiatives: A Review of Challenges, Responses, and Implications - Mbah, Ruth Endam; Hardgrave, Caden Maddox; Mbah, Drusilla Engonwei; Nutt, Alyssa; Russell, Jordan G. (Advances in Social Sciences Research Journal, 2025)
Statistics from 2023 highlight the U.S. as the world’s biggest foreign aid donor, allocating approximately $72 billion in foreign aid, with 61% of this coming from the U.S. Agency for International Development (USAID). Congressional Research Service statistics reveal that in FY 2024, USAID was responsible for over $35 billion (42% of all humanitarian aid, according to the UN) and provided support to 130 countries. By sector, in the FY 2024, USAID spent about $9.9 billion on humanitarian, $9.5 billion on health, $6.9 billion on governance, $3.7 billion on administration, $1.1 billion on agriculture, education, and infrastructure respectively, $0.9 billion on economic growth and $1.2 billion on other aid programs. On January 20th, 2025, a significant vacuum was created by the Trump Administration, unexpectedly imposing USAID cuts via an Executive Order (E.O. 14169). Hence, the focus of this article is to review the impact of USAID budget cuts on global development initiatives and the responses to the cuts. These unexpected cuts have disrupted significant global development initiatives in diverse sectors such as healthcare, education, economic development, democracy and governance, and humanitarian. In response, many recipient countries, NGOs, and development agencies are strategizing for alternative funding. Using the dependency theory as the theoretical framework, the study explores the implications of these cuts. Supporters of this theory argue that because the social construct creates cycles of reliance that impede development, developing nations should instead implement ‘self-reliance.’ Various recipient countries are shifting toward self-reliance as governments seek ways to cope with the void left by USAID cuts. Some experts from recipient countries believe this is a wake-up call for recipient nations to take over their responsibility. Other experts worry that this U.S. policy shift could create a power vacuum, potentially exploited by countries like China, thereby straining U.S. diplomatic ties with recipient nations.